Fund Supported Adjustment Programs and Economic Growth - Knight, Malcolm; Khan, Mohsin (Washington, D.C. : International Monetary Fund, 1985)
This is the first of a group of papers dealing with various aspects of Fund-supported adjustment programs. The other two, The Global Effects of Fund-supported Adjustment Programs by Morris Goldstein and Fund-Supported Programs, Fiscal Policy, and Income Distribution by the Fiscal Affairs Department, will also be published in the Fund's Occasional Paper Series.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet